Phospholipase D δ knock-out mutants re tolerant to severe drought stress - Distefano, Ayelen Mariana (2015)
Phospholipase D (PLD) is involved in different plant processes, ranging from responses to abiotic and biotic stress to plant development. Phospholipase Dδ (PLDδ) is activated in dehydration and salt stress, producing the lipid second messenger phosphatidic acid. In this work we show that pldδ Arabidopsis mutants were more tolerant to severe drought than wild-type plants. PLDδ has been shown to be required for ABA regulation of stomatal closure of isolated epidermal peels. However, there was no significant difference in stomatal conductance at the whole plant level between wild-type and pldδ mutants. Since PLD hydrolyses structural phospholipids, then we looked at membrane integrity. Ion leakage measurements showed that during dehydration of leaf discs pldδ mutant has less membrane degradation compared to the wild-type. We further analyzed the mutants and showed that pldδ have higher mRNA levels of RAB18 and RD29A compared to wild-type plants under normal growth conditions. Transient expression of AtPLDδ in Nicotiana benthamiana plants induced a wilting phenotype. These findings suggest that, in wt plants PLDδ disrupt membranes in severe drought stress and, in the absence of the protein (PLDδ knock-out) might drought-prime the plants, making them more tolerant to severe drought stress. The results are discussed in relation to PLDδ role in guard cell signaling and drought tolerance.